Pengembangan Media Pembelajaran E-Modul Berbasis Flipbook Mengenai Sistem Pernapasan Padamanusia di MI/SD Kelas V - Ritonga, Annida Azhari; Syafitri, Fadya; Widia, Friska; Sazkia, Namira; Siregar, Nurhaliza Ertays (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research aims to explain the results and process of developing flipbook-based e-module learning media on Class V ecosystem material. This research is development research using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation), but this research only reaches the stage development.